Microwave-assisted composite nanomaterial catalyst, preparation method and application thereof

Through the preparation of microwave-assisted composite nanomaterial catalysts, the problem of high precious metal content of existing catalysts is solved, efficient and economical VOC waste gas treatment is achieved, and the catalyst has high catalytic activity and stability.

CN116747899BActive Publication Date: 2025-05-02NANJING UNIV OF SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310569591.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-19
Publication Date
2025-05-02
Estimated Expiration
2043-05-19

AI Technical Summary

Technical Problem

The existing catalysts have high precious metal content, are expensive and prone to poisoning and failure, making it difficult to achieve efficient and economical VOC waste gas treatment.

Method used

The microwave-assisted composite nanomaterial catalyst was used to synthesize silicon carbide composite 4A molecular sieve particles in situ by hydrothermal method, and combined with alumina, Co3O4, CeO2 and ZIF-67 powders supported by single-atom platinum to form a composite nanomaterial catalyst.

Benefits of technology

High catalytic activity and stability are achieved, reducing precious metal loading, reducing costs, and maintaining efficient catalytic performance under long working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116747899B_ABST
    Figure CN116747899B_ABST
Patent Text Reader

Abstract

The present invention discloses a microwave-assisted composite nanomaterial catalyst, a preparation method thereof and an application thereof. The composite nanomaterial catalyst is prepared by drying and calcining a silicon carbide composite 4A molecular sieve raw powder and kaolin loaded with alumina powder, Co3O4 powder, CeO2 powder and ZIF-67 powder loaded with single-atom platinum. In the application of the composite nanomaterial catalyst of the present invention in VOC catalytic oxidation, microwave-assisted heating can greatly reduce the high electricity cost brought by electric heating. At the same time, the catalyst has high catalytic activity and stability, is suitable for catalyzing different VOC waste gas components, and has high application value in the tail gas treatment of petroleum refining production devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of volatile organic compound catalyst materials and relates to a microwave-assisted composite nanomaterial catalyst, a preparation method and application thereof. Background Art

[0002] Volatile organic compounds (VOCs) are a type of pollutant that is prevalent in modern production and life. They mainly refer to organic compounds with a boiling point of 50℃ to 250℃ at normal pressure, a saturated vapor pressure greater than 13.33Pa at room temperature, and easy to evaporate into the atmosphere. According to their chemical structure, they can be divided into aromatic hydrocarbons (benzene, toluene, xylene), unsaturated hydrocarbons, amines, ketones, aldehydes, halogenated hydrocarbons, etc. Volatile organic compounds mainly come from industries such as petrochemicals, paints, papermaking, printing and dyeing, sewage / garbage treatment, and transportation. They are not only highly toxic and volatile, but also form aerosols, photochemical smog, and ozone under sunlight, causing great harm to the atmospheric environment. In addition, when people inhale a certain amount of VOCs, they will feel headaches, nausea, vomiting, and weakness in their limbs in mild cases, and convulsions and coma in severe cases. They will not only damage the liver, kidneys, brain and nervous system, but also cause problems with the human blood and suffer from leukemia or other serious diseases, which are extremely harmful to people's health. Therefore, it is of great research significance to develop simple, efficient, energy-saving and stable VOCs waste gas treatment technology.

[0003] At present, the methods used in VOC treatment technology are mainly divided into physical and chemical methods. The physical method is to remove pollutants by using purification equipment, washing, absorption, condensation, membrane separation and other physical means, but the physical method is only effective when dealing with high concentrations of VOC. Compared with the above methods, the catalytic oxidation method in the chemical method is suitable for the treatment of medium and low concentrations of VOC. It can not only be applied in more scenarios, but also has high conversion efficiency, large gas treatment volume and complete treatment, and low energy consumption in the treatment process, and no secondary pollution. Therefore, the catalytic oxidation method has unique advantages in terms of technology, process, purification efficiency, economic cost and safety, and is suitable for actual industrial production. Catalytic oxidation is the process of oxidizing and decomposing organic pollutants into water, carbon dioxide and other oxides at a relatively low temperature (150-300°C). The core is the catalyst material, which plays a decisive role in the removal efficiency of catalytic oxidation pollutants. Therefore, it is of great significance to develop a low-cost catalyst with high catalytic activity, selectivity and life. Summary of the invention

[0004] In view of the problems that the existing catalysts have high precious metal content, are expensive and are prone to poisoning and failure, the present invention provides a microwave-assisted composite nanomaterial catalyst, a preparation method and its application. The present invention adopts microwave-assisted heating, which can greatly reduce the high electricity cost caused by electric heating, and the prepared catalyst material has high catalytic activity and stability.

[0005] The preparation method of the microwave-assisted composite nanomaterial catalyst of the present invention comprises the following specific steps:

[0006] Step 1: Disperse the pretreated industrial-grade nano-silicon carbide in water by ultrasonic according to the mass fraction of silicon carbide of 1-15%, and 3 ) 3 , NaOH, H 2 O, tetrapropylammonium hydroxide (TPAOH), tetraethyl silicate (TEOS) and NaAlO 2 The mass ratio is 1:0.3~10:50~70:5~10:1~10:0.01~1, adding Al(NO 3 ) 3 , NaOH, H 2 O, TPAOH, TEOS and NaAlO 2 , in-situ synthesis of silicon carbide composite 4A molecular sieve particles by hydrothermal method;

[0007] Step 2: (1) dissolving the PEO-PPO-PEO triblock copolymer (P123) in ethanol to form a copolymer solution, dissolving aluminum isopropoxide in an ethanol solution containing 67% nitric acid to form an aluminum isopropoxide solution, mixing the two solutions in a mass ratio of 1:2:2 between the copolymer, aluminum isopropoxide and nitric acid, and vigorously stirring at room temperature for more than 48 hours. After the reaction is completed, drying to remove the ethanol, placing the dried substance in a muffle furnace, and calcining it at 400-500° C. for 2-6 hours to obtain mesoporous alumina (m-Al 2 O 3 )gel;

[0008] (2) H 2 PtCl 6 The ethanol solution of the mesoporous alumina gel was added to the ethanol solution, stirred at room temperature for more than 48 hours, and the ethanol was removed by drying after the reaction was completed. Finally, the temperature was increased to 400-500°C at a heating rate of 1-2°C / min and calcined for 2-6 hours to obtain alumina powder loaded with single-atom platinum (Pt-Al 2 O 3 ), recorded as component A;

[0009] Step 3: Co(NO 3 ) 2 6H 2O and hexamethylenetetramine (C 6 H 12 N 4 , urotropine) were dissolved in a mixed solution of deionized water and ethanol to form Co(NO 3 ) 2 Solution and hexamethylenetetramine solution, according to Co(NO 3 ) 2 6H 2 The molar ratio of O and hexamethylenetetramine is 1:2. The two solutions are stirred until fully mixed and then subjected to hydrothermal reaction. After the reaction is completed, the solution is naturally cooled to room temperature, and the supernatant is removed by filtration under reduced pressure. The solution is repeatedly washed with deionized water and anhydrous ethanol, and then vacuum dried. Finally, the solution is placed in a tube furnace and calcined at 400-500°C for 2h to obtain Co 3 O 4 Powder, i.e. component B;

[0010] Step 4: Press Ce(NO 3 ) 3 and H 2 O 2 The molar ratio of Ce(NO 3 ) 3 Add H 2 O 2 The solution was prepared, the pH of the reaction system was adjusted to 4-6, the reaction was continued under stirring, and after the reaction was completed, ammonia water was added dropwise to completely precipitate the solution, and the solution was washed, filtered, dried, ground, and calcined at 400-500°C for 2h to obtain CeO 2 Powder, i.e. component C;

[0011] Step 5: Mix the silicon carbide composite 4A molecular sieve powder and kaolin in a mass ratio of 3 to 5:1, and then add alumina powder loaded with single atomic platinum, Co 3 O 4 Powder, CeO 2 The powder and ZIF-67 powder are mixed evenly to form a spherical particle with uniform particle size, first dried at 100-200°C for 8-10 hours, and then calcined at 400-600°C for 2-8 hours to obtain a composite nanomaterial catalyst. The alumina powder loaded with single atomic platinum, Co 3 O 4 Powder, CeO 2 The mass ratio of powder and ZIF-67 powder is 0.4-0.6: 0.2-0.3: 0.05-0.1: 0.15-0.3, and the alumina powder loaded with single atomic platinum, Co 3 O 4 Powder, CeO 2 The total mass of the powder and the ZIF-67 powder accounts for 0.05-10% of the total mass of the silicon carbide composite 4A molecular sieve original powder and kaolin.

[0012] Preferably, in step 1, the pretreatment method of industrial-grade nano-silicon carbide is specifically as follows: washing the industrial-grade nano-silicon carbide with water, alkali, and ethanol in sequence under ultrasound, centrifuging after each ultrasonic washing for 20 to 40 minutes, repeating with different solvents 2 to 3 times, and the alkali used is a sodium hydroxide aqueous solution with a pH of 5.

[0013] Preferably, in step 1, the hydrothermal temperature is 100° C. and the hydrothermal reaction time is 6 h.

[0014] Preferably, in step 1, the mass fraction of silicon carbide is 4-6%, Al(NO 3 ) 3 , NaOH, H 2 O, TPAOH, TEOS and NaAlO 2 The mass ratio is 1:0.6~3.3:52~60:4.9~7:2~4.3:0.04~0.2.

[0015] Preferably, in step 2 (1), the concentration of the copolymer in the copolymer solution is 0.06 to 0.12 g L -1 ; In the aluminum isopropoxide solution, the concentration of aluminum isopropoxide is 0.1-0.3 g L -1 .

[0016] Preferably, in step 2 (1), the drying temperature is 60 to 80° C. and the drying time is 48 to 72 hours.

[0017] Preferably, in step 2 (2), H 2 PtCl 6 In ethanol solution, H 2 PtCl 6 The mass concentration is 0.1~10%.

[0018] Preferably, in step 2 (2), the loading amount of Pt in the alumina powder loaded with single-atom platinum is 0.1 to 10%.

[0019] Preferably, in step 3, Co(NO 3 ) 2 The concentration of the solution is 0.02~0.1mol L -1 The concentration of hexamethylenetetramine solution is 0.05~0.15mol L -1 .

[0020] Preferably, in step 3, the vacuum drying temperature is 60° C. and the drying time is 10 h.

[0021] Preferably, in step 4, the washing method is to wash with deionized water and ethanol 2 to 3 times respectively, the drying temperature is 60° C., and the drying time is 10 hours.

[0022] Preferably, in step 5, the preparation method of ZIF-67 is as follows: according to Co(NO 3 ) 2 6H 2 The mass ratio of O and 2-methylimidazole is 1:1-5, and the concentration is 0.05-0.15 mol L -1 Co(NO 3 ) 2 6H 2 O methanol solution was injected into the concentration of 0.5-1.0 mol L -1 The mixture was added into a 2-methylimidazole (MeIM) methanol solution and stirred at room temperature for 1.5 to 3.0 h. After the reaction, the precipitate was centrifuged, washed with ethanol, and vacuum dried at 60 to 80° C. overnight to obtain ZIF-67 powder, which was recorded as component D.

[0023] The invention provides a composite nano material catalyst prepared by the preparation method.

[0024] Furthermore, the present invention provides an application of the above-mentioned composite nanomaterial catalyst in microwave-assisted VOC catalytic oxidation, specifically: introducing air and VOC tail gas, and heating the catalytic environment to the optimal catalytic reaction temperature of 250-320°C under microwave-assisted heating to carry out catalytic oxidation reaction.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The method for synthesizing the nanocomposite catalyst prepared by the present invention is mature and universal, and has wide applicability. It can be extended to the preparation of similar materials, has good process repeatability, is relatively safe, and has relatively high operability for large-scale synthesis. Unlike traditional electric heating, microwave heating is selective, allowing the catalyst to more effectively utilize microwave energy to improve the efficiency of catalytic oxidation of VOC gases. The in-situ grown silicon carbide and molecular sieve can improve the utilization rate of microwave energy, solving the problem of uneven composite during the molecular sieve forming process.

[0027] (2) The composite nanomaterial catalyst of the present invention has a significantly reduced precious metal loading while maintaining a good catalytic effect, thereby reducing costs. The catalyst can maintain high catalytic activity and structural integrity under long-term working conditions, thereby improving the stability and life of the material.

[0028] (3) The silicon carbide synergistic molecular sieve loaded noble metal single atom catalyst of the present invention is a new type of composite material catalyst. The nanomaterial components are optimized and can be applied to the catalysis of different VOC waste gas components. It can ensure good catalytic effects on conventional ethylbenzene, styrene, xylene and other benzene components at temperatures below 250°C, especially in the tail gas part of petroleum refining production equipment. It has high application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The (Pt-Al 2 O 3 ) Actual picture of the powder.

[0030] Figure 2 This is a physical picture of the mixed powder sample of components A, B, C and D prepared in Example 3.

[0031] Figure 3 This is a low-resolution transmission electron microscope (TEM) image of the composite nanocatalyst prepared in Example 3.

[0032] Figure 4 This is a high-resolution transmission electron microscope (TEM) image of the composite nanocatalyst prepared in Example 3.

[0033] Figure 5 This is a low-resolution transmission electron microscope (TEM) image of the composite nanocatalyst prepared in Example 3 after catalytic reaction for 30 days.

[0034] Figure 6 This is a low-resolution transmission electron microscope (TEM) image of the composite nanocatalyst prepared in Example 3 after catalytic reaction for 30 days.

[0035] Figure 7 This is a high-resolution transmission electron microscope (TEM) image of the composite nanocatalyst prepared in Example 3 after catalytic reaction for 30 days.

[0036] Figure 8 This is a high-resolution transmission electron microscope (TEM) image of the composite nanocatalyst prepared in Example 3 after catalytic reaction for 30 days. DETAILED DESCRIPTION

[0037] The present invention is further described in detail below through specific embodiments and drawings.

[0038] In the following examples, the PEO-PPO-PEO used was purchased from Tianjin Xiensi Biochemical Technology Co., Ltd. and had a molecular weight of 3,500.

[0039] Example 1

[0040] (1) Industrial-grade nano-silicon carbide was washed with water, alkali, and alcohol (washed under ultrasound for 30 minutes and then centrifuged, and the washing was repeated twice with different solvents. The water used was deionized water, the alkali used was a sodium hydroxide aqueous solution with a pH of 5, and the alcohol used was analytical grade ethanol) and dispersed in water for ultrasonic dispersion. A certain proportion of the precursor Al(NO 3 ) 3 , NaOH, H2 O, TPAOH, TEOS and NaAlO 2 Silicon carbide composite 4A molecular sieve was synthesized in situ by hydrothermal method, and then filtered, washed and dried with deionized water to obtain silicon carbide composite 4A molecular sieve; Al(NO 3 ) 3 , NaOH, H 2 O, TPAOH, TEOS, NaAlO 2 The mass ratio is 1:0.6:60:7:3.2:0.04, and the mass fraction of silicon carbide in water is 4%.

[0041] (2) 2.1 g of PEO-PPO-PEO triblock copolymer (P123) was dissolved in ethanol, and 4.08 g of aluminum isopropoxide was dissolved in ethanol containing 3.5 mL of 67% nitric acid (the alcohol used was analytical grade ethanol), with concentrations of 0.08 g L -1 and 0.15 g L -1 . Then 30 mL of the two solutions were mixed and stirred vigorously to combine, and the volume ratio of the two solutions was 1:1.2. A layer of PE film was covered on the mixed solution, stirred at room temperature for 48 hours, and then placed in a constant temperature oven at 60°C for 72 hours to completely evaporate the ethanol. The dried material was placed in a muffle furnace and calcined at 400°C for 4 hours to obtain mesoporous alumina (m-Al 2 O 3 ) gel; 2% by mass of H 2 PtCl 6 The ethanol solution of the mesoporous alumina was added to the ethanol solution containing the mesoporous alumina, and stirred at room temperature for 48 hours, and then placed in a constant temperature oven at 60°C for 72 hours to completely evaporate the ethanol; finally, the temperature was raised to 400°C at a heating rate of 1°C / min and calcined for 4 hours to obtain alumina loaded with single atomic platinum (Pt-Al 2 O 3 ) powder (Pt loading is 0.5%), namely component A.

[0042] (3) 37.5 mmolCo(NO 3 ) 2 6H 2 O and 75mmol hexamethylenetetramine (C 6 H 12 N 4 )(Urotropine) were dissolved in a mixed solution of deionized water and ethanol (the alcohol used was analytical grade ethanol) with a concentration of 0.05 mol / L -1 and 0.1 mol L -1. Then, 250 mL of the two solutions were fully mixed and magnetically stirred for 1 hour. After that, the fully mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and placed in an oven for reaction. After the reaction was completed, the precipitate was obtained after natural cooling. The supernatant was removed by vacuum filtration, and after repeated washing with deionized water and anhydrous ethanol, it was placed in a vacuum drying oven and dried at 60°C for 10 hours. Finally, the obtained product was placed in a tubular furnace and calcined at 450°C for 2 hours to obtain Co 3 O 4 Powder, i.e. component B;

[0043] (4) Put 5g Ce(NO 3 ) 3 Dissolve in deionized water to prepare a solution with a concentration of 0.1 mol L -1 , to 60mL Ce(NO 3 ) 3 Slowly add 5 mL of H 2 O 2 Solution, adjust the pH of the reaction system to 5, and place it on a magnetic stirrer for continuous stirring. After the reaction is completed, titrate the ammonia solution into the solution at a rate of 0.05 mL / s until the pH value of the solution reaches 9. After complete precipitation, wash the precipitate with deionized water several times. Add ethanol and stir thoroughly, and then filter the precipitate with a vacuum pump to obtain a precipitate. Place the precipitate in a beaker and dry it in a constant temperature oven at 60°C for 10 hours. Grind the dried solid in a mortar, and calcine it in a muffle furnace at 400°C for 2 hours to obtain CeO 2 Powder, i.e. component C;

[0044] (5) Put Co(NO 3 ) 2 6H 2 O dissolved in methanol to form a transparent solution (0.15 mol L -1 ), which was then injected into a methanol solution of 2-methylimidazole (MeIM) (0.5 mol L -1 ), stirred at room temperature for 2 h, the resulting precipitate was centrifuged, washed several times with ethanol, and dried overnight in a vacuum at 70 ° C to obtain ZIF-67 powder, i.e. component D; Zn(NO 3 ) 2 6H 2 O and Ce(NO 3 ) 3 6H 2 O mass ratio is 1:1.

[0045] (6) Silicon carbide composite 4A molecular sieve powder and kaolin are mixed evenly in a mass ratio of 5:1, and components A, B, C and D are added, the total mass of components A, B, C and D is 1.5% of the total mass of molecular sieve powder and kaolin, and spherical particles with uniform particle size are prepared. After drying and calcination, the composite nanomaterial catalyst of the present invention is obtained, the product mass is 1000g, and the mass ratio of components A, B, C and D is 0.5:0.3:0.05:0.15. The drying and calcination temperatures are 120°C and 550°C, and the time is 12h and 5h respectively.

[0046] Example 2

[0047] (1) Industrial-grade nano-silicon carbide was washed with water, alkali, and alcohol (washed under ultrasound for 30 minutes and then centrifuged, and the washing was repeated twice with different solvents. The water used was deionized water, the alkali used was a sodium hydroxide aqueous solution with a pH of 5, and the alcohol used was analytical grade ethanol) and dispersed in water for ultrasonic dispersion. A certain proportion of the precursor Al(NO 3 ) 3 , NaOH, H 2 O, TPAOH, TEOS and NaAlO 2 Silicon carbide composite 4A molecular sieve particles were synthesized in situ by hydrothermal method, and then filtered, washed and dried with deionized water to obtain silicon carbide composite 4A molecular sieve raw powder; Al(NO 3 ) 3 , NaOH, H 2 O, TPAOH, TEOS, NaAlO 2 The mass ratio is 1:0.6:60:7:3.2:0.04, and the mass fraction of silicon carbide in water is 4%.

[0048] (2) 2.1 g of PEO-PPO-PEO triblock copolymer (P123) was dissolved in ethanol, and 4.08 g of aluminum isopropoxide was dissolved in 4 mL of ethanol containing 67% nitric acid (the alcohol used was analytical grade ethanol), with concentrations of 0.08 g L -1 and 0.15 g L -1 . Then 30 mL of the two solutions were mixed and stirred vigorously to combine the two solutions in a volume ratio of 1:1.2. A layer of PE film was covered on the mixed solution, stirred at room temperature for 48 hours, and then placed in a constant temperature oven at 60°C for 72 hours to completely evaporate the ethanol. The dried material was placed in a muffle furnace and calcined at 400°C for 4 hours to obtain mesoporous alumina (m-Al 2 O 3 ) gel; 2% by mass of H 2 PtCl 6The ethanol solution of the mesoporous alumina was added to the ethanol solution containing the mesoporous alumina, and stirred at room temperature for 48 hours, and then placed in a constant temperature oven at 60°C for 72 hours to completely evaporate the ethanol; finally, the temperature was raised to 400°C at a heating rate of 1°C / min and calcined for 4 hours to obtain alumina loaded with single atomic platinum (Pt-Al 2 O 3 ) powder (Pt loading is 0.5%), namely component A.

[0049] (3) 37.5 mmolCo(NO 3 ) 2 6H 2 O and 75mmol hexamethylenetetramine (C 6 H 12 N 4 )(Urotropine) were dissolved in a mixed solution of deionized water and ethanol (the alcohol used was analytical grade ethanol) with a concentration of 0.05 mol L -1 and 0.1 mol L -1 . Then, 250 mL of the two solutions were fully mixed and magnetically stirred for 1 hour. The fully mixed solution was then transferred to a polytetrafluoroethylene-lined hydrothermal reactor and then placed in an oven for reaction. After the reaction was completed, the solution was taken out and cooled naturally to obtain a precipitate. The supernatant was removed by vacuum filtration, and after repeated washing with deionized water and anhydrous ethanol, it was placed in a vacuum drying oven and dried at 60°C for 10 hours. Finally, the obtained product was placed in a tubular furnace and calcined at 450°C for 2 hours to obtain Co 3 O 4 Powder, i.e. component B;

[0050] (4) Put 5g Ce(NO 3 ) 3 Dissolve in deionized water to prepare a solution with a concentration of 0.1 mol L -1 , to 60mL Ce(NO 3 ) 3 Slowly add 5 mL of H 2 O 2 Solution, adjust the pH of the reaction system to 5, and place it on a magnetic stirrer for continuous stirring. After the reaction is completed, titrate the ammonia solution into the solution at a rate of 0.05 mL / s until the pH value of the solution reaches 9. After complete precipitation, wash the precipitate with deionized water several times. Add ethanol and stir thoroughly, and then filter the precipitate with a vacuum pump to obtain a precipitate. Place the precipitate in a beaker and dry it in a constant temperature oven at 60°C for 10 hours. Grind the dried solid in a mortar, and calcine it in a muffle furnace at 400°C for 2 hours to obtain CeO 2 Powder, i.e. component C;

[0051] (5) Put Co(NO3 ) 2 6H 2 O dissolved in methanol to form a transparent solution (0.15 mol L -1 ), which was then injected into a methanol solution of 2-methylimidazole (MeIM) (0.5 mol L -1 ), stirred at room temperature for 2 h, the resulting precipitate was centrifuged, washed several times with ethanol, and dried overnight in a vacuum at 70 ° C to obtain ZIF-67 powder, i.e. component D; Zn(NO 3 ) 2 6H 2 O and Ce(NO 3 ) 3 6H 2 O mass ratio is 1:1.

[0052] (6) Silicon carbide composite 4A molecular sieve powder and kaolin are mixed evenly in a mass ratio of 5:1, and components A, B, C and D are added, the total mass of components A, B, C and D is 1.5% of the total mass of molecular sieve powder and kaolin, and spherical particles with uniform particle size are prepared. After drying and calcination, the composite nanomaterial catalyst of the present invention is obtained, the product mass is 1000g, and the mass ratio of components A, B, C and D is 0.45:0.25:0.1:0.2. The drying and calcination temperatures are 120°C and 550°C, and the time is 12h and 5h, respectively.

[0053] Example 3

[0054] (1) Industrial-grade nano-silicon carbide was washed with water, alkali, and alcohol (washed under ultrasound for 30 minutes and then centrifuged, and the washing was repeated 3 times with different solvents. The water used was deionized water, the alkali used was a sodium hydroxide aqueous solution with a pH of 5, and the alcohol used was analytical grade ethanol) and dispersed in water for ultrasonic dispersion. A certain proportion of the precursor Al(NO 3 ) 3 , NaOH, H 2 O, TPAOH, TEOS and NaAlO 2 Silicon carbide composite 4A molecular sieve particles were synthesized in situ by hydrothermal method, and then filtered, washed and dried with deionized water to obtain silicon carbide composite 4A molecular sieve raw powder; Al(NO 3 ) 3 , NaOH, H 2 O, TPAOH, TEOS, NaAlO 2 The mass ratio is 1:1.7:52:6.5:4.3:0.2, and the mass fraction of silicon carbide in water is 4.5%.

[0055] (2) 2.1 g of PEO-PPO-PEO triblock copolymer (P123) was dissolved in ethanol, and 4.08 g of aluminum isopropoxide was dissolved in 4 mL of ethanol containing 67% nitric acid (the alcohol used was analytical grade ethanol), with concentrations of 0.08 g L -1 and 0.15 g L -1 . Then 30 mL of the two solutions were mixed and stirred vigorously to combine the two solutions in a volume ratio of 1:1.2. A layer of PE film was covered on the mixed solution, stirred at room temperature for 48 hours, and then placed in a constant temperature oven at 60°C for 72 hours to completely evaporate the ethanol. The dried material was placed in a muffle furnace and calcined at 400°C for 4 hours to obtain mesoporous alumina (m-Al 2 O 3 ) gel; 2% by mass of H 2 PtCl 6 The ethanol solution of the mesoporous alumina was added to the ethanol solution containing the mesoporous alumina, and stirred at room temperature for 48 hours, and then placed in a constant temperature oven at 60°C for 72 hours to completely evaporate the ethanol; finally, the temperature was raised to 400°C at a heating rate of 1°C / min and calcined for 4 hours to obtain alumina loaded with single atomic platinum (Pt-Al 2 O 3 ) powder (Pt loading is 0.5%), namely component A.

[0056] (3) 37.5 mmolCo(NO 3 ) 2 6H 2 O and 75mmol hexamethylenetetramine (C 6 H 12 N 4 )(Urotropine) were dissolved in a mixed solution of deionized water and ethanol (the alcohol used was analytical grade ethanol) with a concentration of 0.05 mol L -1 and 0.1 mol L -1 . Then 250mL of the two solutions were fully mixed and magnetically stirred for 1h, and then the fully mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor, and then placed in an oven for reaction. After the reaction was completed, the precipitate was obtained after natural cooling. The supernatant was removed by vacuum filtration, and after repeated washing with deionized water and anhydrous ethanol, it was placed in a vacuum drying oven at 60°C for 10h. Finally, the obtained product was placed in a tubular furnace and calcined at 450°C for 2h to obtain Co 3 O 4 Powder, i.e. component B;

[0057] (4) Put 5g Ce(NO 3 ) 3Dissolve in deionized water to prepare a solution with a concentration of 0.1 mol L -1 , to 60mL Ce(NO 3 ) 3 Slowly add 5 mL of H 2 O 2 Solution, adjust the pH of the reaction system to 5, and place it on a magnetic stirrer for continuous stirring. After the reaction is completed, titrate the ammonia solution into the solution at a rate of 0.05 mL / s until the pH value of the solution reaches 9. After complete precipitation, wash the precipitate with deionized water several times. Add ethanol and stir thoroughly, and then filter the precipitate with a vacuum pump to obtain a precipitate. Place the precipitate in a beaker and dry it in a constant temperature oven at 60°C for 10 hours. Grind the dried solid in a mortar, and calcine it in a muffle furnace at 400°C for 2 hours to obtain CeO 2 Powder, i.e. component C;

[0058] (5) Put Co(NO 3 ) 2 6H 2 O dissolved in methanol to form a transparent solution (0.15 mol L -1 ), which was then injected into a methanol solution of 2-methylimidazole (MeIM) (0.5 mol L -1 ), stirred at room temperature for 2 h, the resulting precipitate was centrifuged, washed several times with ethanol, and dried overnight in a vacuum at 70 ° C to obtain ZIF-67 powder, i.e. component D; Zn(NO 3 ) 2 6H 2 O and Ce(NO 3 ) 3 6H 2 O mass ratio is 1:1.

[0059] (6) Silicon carbide composite 4A molecular sieve powder and kaolin are mixed evenly in a mass ratio of 5:1, and components A, B, C and D are added, the total mass of components A, B, C and D is 1.5% of the total mass of molecular sieve powder and kaolin, and spherical particles with uniform particle size are prepared. After drying and calcination, the composite nanomaterial catalyst of the present invention is obtained, the product mass is 1000g, and the mass ratio of components A, B, C and D is 0.6:0.20:0.05:0.15. The drying and calcination temperatures are 120°C and 550°C, and the time is 12h and 5h respectively.

[0060] Example 4

[0061] (1) Industrial-grade nano-silicon carbide was washed with water, alkali, and alcohol (washed under ultrasound for 30 minutes and then centrifuged, and the washing was repeated 3 times with different solvents. The water used was deionized water, the alkali used was a sodium hydroxide aqueous solution with a pH of 5, and the alcohol used was analytical grade ethanol) and dispersed in water for ultrasonic dispersion. A certain proportion of the precursor Al(NO 3 ) 3 , NaOH, H 2 O, TPAOH, TEOS and NaAlO 2 Silicon carbide composite 4A molecular sieve particles were synthesized in situ by hydrothermal method, and then filtered, washed and dried with deionized water to obtain silicon carbide composite 4A molecular sieve raw powder; Al(NO 3 ) 3 , NaOH, H 2 O, TPAOH, TEOS, NaAlO 2 The mass ratio is 1:3.3:60:5.2:2.0:0.12, and the mass fraction of silicon carbide in water is 6%.

[0062] (2) 2.1 g of PEO-PPO-PEO triblock copolymer (P123) was dissolved in ethanol, and 4.08 g of aluminum isopropoxide was dissolved in ethanol containing 3.5 mL of 67% nitric acid (the alcohol used was analytical grade ethanol), with concentrations of 0.08 g L -1 and 0.15 g L -1 . Then 30 mL of the two solutions were mixed and stirred vigorously to combine the two solutions in a volume ratio of 1:1.2. A layer of PE film was covered on the mixed solution, stirred at room temperature for 48 hours, and then placed in a constant temperature oven at 60°C for 72 hours to completely evaporate the ethanol. The dried material was placed in a muffle furnace and calcined at 400°C for 4 hours to obtain mesoporous alumina (m-Al 2 O 3 ) gel; 2% by mass of H 2 PtCl 6 The ethanol solution of the mesoporous alumina was added to the ethanol solution containing the mesoporous alumina, and stirred at room temperature for 48 hours, and then placed in a constant temperature oven at 60°C for 72 hours to completely evaporate the ethanol; finally, the temperature was raised to 400°C at a heating rate of 1°C / min and calcined for 4 hours to obtain alumina loaded with single atomic platinum (Pt-Al 2 O 3 ) powder (Pt loading is 0.5%), namely component A.

[0063] (3) 37.5 mmolCo(NO 3 ) 2 6H 2 O and 75mmol hexamethylenetetramine (C 6 H12 N 4 )(Urotropine) were dissolved in a mixed solution of deionized water and ethanol (the alcohol used was analytical grade ethanol) with a concentration of 0.05 mol L -1 and 0.1 mol L -1 . Then, 250 mL of the two solutions were fully mixed and magnetically stirred for 1 hour. The fully mixed solution was then transferred to a polytetrafluoroethylene-lined hydrothermal reactor and then placed in an oven for reaction. After the reaction was completed, the solution was taken out and cooled naturally to obtain a precipitate. The supernatant was removed by vacuum filtration, and after repeated washing with deionized water and anhydrous ethanol, it was placed in a vacuum drying oven and dried at 60°C for 10 hours. Finally, the obtained product was placed in a tubular furnace and calcined at 450°C for 2 hours to obtain Co 3 O 4 Powder, i.e. component B;

[0064] (4) Put 5g Ce(NO 3 ) 3 Dissolve in deionized water to prepare a solution with a concentration of 0.1 mol L -1 , to 60mL Ce(NO 3 ) 3 Slowly add 5 mL of H 2 O 2 Solution, adjust the pH of the reaction system to 5, and place it on a magnetic stirrer for continuous stirring. After the reaction is completed, titrate the ammonia solution into the solution at a rate of 0.05 mL / s until the pH value of the solution reaches 9. After complete precipitation, wash the precipitate with deionized water several times. Add ethanol and stir thoroughly, and then filter the precipitate with a vacuum pump to obtain a precipitate. Place the precipitate in a beaker and dry it in a constant temperature oven at 60°C for 10 hours. Grind the dried solid in a mortar, and calcine it in a muffle furnace at 400°C for 2 hours to obtain CeO 2 Powder, i.e. component C;

[0065] (5) Put Co(NO 3 ) 2 6H 2 O dissolved in methanol to form a transparent solution (0.15 mol L -1 ), which was then injected into a methanol solution of 2-methylimidazole (MeIM) (0.5 mol L -1 ), stirred at room temperature for 2 h, the resulting precipitate was centrifuged, washed several times with ethanol, and dried overnight in a vacuum at 70 ° C to obtain ZIF-67 powder, i.e. component D; Zn(NO 3 ) 2 6H 2 O and Ce(NO 3 ) 3 6H2 O mass ratio is 1:1.

[0066] (6) Silicon carbide composite 4A molecular sieve powder and kaolin are mixed evenly in a mass ratio of 5:1, and components A, B, C and D are added, the total mass of components A, B, C and D is 1.5% of the total mass of molecular sieve powder and kaolin, and spherical particles with uniform particle size are prepared. After drying and calcination, the composite nanomaterial catalyst of the present invention is obtained, the product mass is 1000g, and the mass ratio of components A, B, C and D is 0.4:0.3:0.05:0.25. The drying and calcination temperatures are 120°C and 550°C, and the time is 12h and 5h, respectively.

[0067] Example 5

[0068] (1) Industrial-grade nano-silicon carbide was washed with water, alkali, and alcohol (washed under ultrasound for 30 minutes and then centrifuged, and the washing was repeated 3 times with different solvents. The water used was deionized water, the alkali used was a sodium hydroxide aqueous solution with a pH of 5, and the alcohol used was analytical grade ethanol) and dispersed in water for ultrasonic dispersion. A certain proportion of the precursor Al(NO 3 ) 3 , NaOH, H 2 O, TPAOH, TEOS and NaAlO 2 Silicon carbide composite 4A molecular sieve particles were synthesized in situ by hydrothermal method, and then filtered, washed and dried with deionized water to obtain silicon carbide composite 4A molecular sieve raw powder; Al(NO 3 ) 3 , NaOH, H2O, TPAOH, TEOS, NaAlO 2 The mass ratio is 1:1.5:57:4.9:2.0:0.14, and the mass fraction of silicon carbide in water is 4%.

[0069] (2) 2.1 g of PEO-PPO-PEO triblock copolymer (P123) was dissolved in ethanol, and 4.08 g of aluminum isopropoxide was dissolved in ethanol containing 3.5 mL of 67% nitric acid (the alcohol used was analytical grade ethanol), with concentrations of 0.08 g L -1 and 0.15 g L -1 . Then 30 mL of the two solutions were mixed and stirred vigorously to combine the two solutions in a volume ratio of 1:1.2. A layer of PE film was covered on the mixed solution, stirred at room temperature for 48 hours, and then placed in a constant temperature oven at 60°C for 72 hours to completely evaporate the ethanol. The dried material was placed in a muffle furnace and calcined at 400°C for 4 hours to obtain mesoporous alumina (m-Al 2 O 3 ) gel; 2% by mass of H 2 PtCl6 The ethanol solution of the mesoporous alumina was added to the ethanol solution containing the mesoporous alumina, and stirred at room temperature for 48 hours, and then placed in a constant temperature oven at 60°C for 72 hours to completely evaporate the ethanol; finally, the temperature was raised to 400°C at a heating rate of 1°C / min and calcined for 4 hours to obtain alumina loaded with single atomic platinum (Pt-Al 2 O 3 ) powder (Pt loading is 0.5%), namely component A.

[0070] (3) 37.5 mmolCo(NO 3 ) 2 6H 2 O and 75mmol hexamethylenetetramine (C 6 H 12 N 4 )(Urotropine) were dissolved in a mixed solution of deionized water and ethanol (the alcohol used was analytical grade ethanol) with a concentration of 0.05 mol L -1 and 0.1 mol L -1 . Then, 250 mL of the two solutions were fully mixed and magnetically stirred for 1 hour. The fully mixed solution was then transferred to a polytetrafluoroethylene-lined hydrothermal reactor and then placed in an oven for reaction. After the reaction was completed, the solution was taken out and cooled naturally to obtain a precipitate. The supernatant was removed by vacuum filtration, and after repeated washing with deionized water and anhydrous ethanol, it was placed in a vacuum drying oven and dried at 60°C for 10 hours. Finally, the obtained product was placed in a tubular furnace and calcined at 450°C for 2 hours to obtain Co 3 O 4 Powder, i.e. component B;

[0071] (4) Put 5g Ce(NO 3 ) 3 Dissolve in deionized water to prepare a solution with a concentration of 0.1 mol L -1 , to 60mL Ce(NO 3 ) 3 Slowly add 5 mL of H 2 O 2 Solution, adjust the pH of the reaction system to 5, and place it on a magnetic stirrer for continuous stirring. After the reaction is completed, titrate the ammonia solution into the solution at a rate of 0.05 mL / s until the pH value of the solution reaches 9. After complete precipitation, wash the precipitate with deionized water several times. Add ethanol and stir thoroughly, then filter the precipitate with a vacuum pump to obtain a precipitate. Place the precipitate in a beaker and dry it in a constant temperature oven at 60°C for 10 hours. Grind the dried solid in a mortar, and calcine it in a muffle furnace at 400°C for 2 hours to obtain CeO 2 Powder, i.e. component C;

[0072] (5) Put Co(NO 3 ) 2 6H 2 O dissolved in methanol to form a transparent solution (0.15 mol L -1 ), which was then injected into a methanol solution of 2-methylimidazole (MeIM) (0.5 mol L -1 ), stirred at room temperature for 2 h, the resulting precipitate was centrifuged, washed several times with ethanol, and dried overnight in a vacuum at 70 ° C to obtain ZIF-67 powder, i.e. component D; Zn(NO 3 ) 2 6H 2 O and Ce(NO 3 ) 3 6H 2 O mass ratio is 1:1.

[0073] (6) Silicon carbide composite 4A molecular sieve powder and kaolin are mixed evenly in a mass ratio of 5:1, and components A, B, C and D are added, the total mass of components A, B, C and D is 1.5% of the total mass of molecular sieve powder and kaolin, and spherical particles with uniform particle size are prepared. After drying and calcining, the composite nanomaterial catalyst of the present invention is obtained, the product mass is 1000g, and the mass ratio of components A, B, C and D is 0.4:0.2:0.1:0.3. The drying and calcining temperatures are 120°C and 550°C, and the time is 12h and 5h respectively.

[0074] Table 1: Catalytic effect of catalysts in various examples on VOC tail gas

[0075]

[0076] The catalyst activity was evaluated in a fixed bed reactor tube with a diameter of 1 cm and a catalyst loading mass of about 0.18 g. The tube was ventilated for 10 minutes to balance the gas components and eliminate the residual gas components in the tube. 3 / h, VOC tail gas nitrogen loaded with benzene, toluene, ethylbenzene, styrene, xylene, and isopropylbenzene (GBW(E)062160); then under microwave-assisted heating, the catalytic environment can be quickly heated to the optimal catalytic reaction temperature of 250-320°C, and the common VOC gas components in the VOC tail gas are converted into carbon dioxide and water through high-temperature catalytic pyrolysis reaction. Under different catalytic time, the gas equilibrium is maintained for 2 minutes, and the gas components are collected. The total atomic weight of the reaction product is measured by gas chromatography to calculate the catalytic conversion efficiency. The test results are shown in Table 1. The catalyst sample has a good heating effect under microwave assistance and good catalytic activity. The conversion rate can still be maintained at 98% at a low temperature of 250°C for 30 days. In addition, from Figure 5-8It can be observed that after a long period of high-temperature catalytic reaction, the morphology of the composite nanocatalyst is no longer obvious small particles, but the crystallinity of the material is still good, thus ensuring the material's good catalytic activity and long life.

Claims

1. A method for preparing a microwave-assisted composite nanomaterial catalyst, characterized in that: The specific steps are as follows: Step 1: According to the mass fraction of silicon carbide of 1-15%, the pretreated industrial-grade nano-silicon carbide is ultrasonically dispersed in water, and Al(NO3)3, NaOH, H2O, TPAOH, TEOS and NaAlO2 are added according to the mass ratio of Al(NO3)3, NaOH, H2O, TPAOH, TEOS and NaAlO2 of 1:0.3-10:50-70:5-10:1-10:0.01-1, and silicon carbide composite 4A molecular sieve particles are synthesized in situ by hydrothermal method; Step 2: (1) dissolving the PEO-PPO-PEO triblock copolymer in ethanol to form a copolymer solution, dissolving aluminum isopropoxide in an ethanol solution containing 67% nitric acid to form an aluminum isopropoxide solution, mixing the two solutions in a mass ratio of 1:2:2 between the copolymer, aluminum isopropoxide and nitric acid, and vigorously stirring at room temperature for more than 48 hours. After the reaction is completed, drying to remove the ethanol, placing the dried substance in a muffle furnace, and calcining at 400-500° C. for 2-6 hours to obtain a mesoporous alumina gel; (2) adding an ethanol solution of H2PtCl6 to an ethanol solution containing mesoporous alumina gel, stirring at room temperature for more than 48 hours, drying to remove ethanol after the reaction is completed, and finally heating to 400-500°C at a heating rate of 1-2°C / min and calcining for 2-6 hours to obtain alumina powder loaded with single atomic platinum; Step 3: Dissolve Co(NO3)2·6H2O and hexamethylenetetramine in a mixed solution of deionized water and ethanol respectively to form a Co(NO3)2 solution and a hexamethylenetetramine solution. Stir the two solutions until they are fully mixed at a molar ratio of Co(NO3)2·6H2O to hexamethylenetetramine of 1:2, and then perform a hydrothermal reaction. After the reaction is completed, naturally cool to room temperature, filter under reduced pressure to remove the supernatant, repeatedly wash with deionized water and anhydrous ethanol, and vacuum dry. Finally, place in a tube furnace and calcine at 400~500℃ for 2 h to obtain Co3O4 powder. Step 4: Add H2O2 solution to Ce (NO3)3 solution at a molar ratio of Ce (NO3)3 to H2O2 of 2:1, adjust the pH of the reaction system to 4-6, continue stirring the reaction, add ammonia water after the reaction is completed to completely precipitate, wash, filter, dry, grind, and calcine at 400-500 °C for 2h to obtain CeO2 powder; Step 5: Mix the silicon carbide composite 4A molecular sieve raw powder and kaolin in a mass ratio of 3-5:1, then add alumina powder, Co3O4 powder, CeO2 powder and ZIF-67 powder loaded with single atomic platinum, mix them evenly and make them into spheres with uniform particle size, first dry them at 100-200°C for 8-10h, and then calcine them at 400-600°C for 2-8h to obtain a composite nanomaterial catalyst, wherein the mass ratio of the alumina powder, Co3O4 powder, CeO2 powder and ZIF-67 powder loaded with single atomic platinum is 0.4-0.6: 0.2-0.3: 0.05-0.1: 0.15-0.3, and the total mass of the alumina powder, Co3O4 powder, CeO2 powder and ZIF-67 powder loaded with single atomic platinum accounts for 0.05-10% of the total mass of the silicon carbide composite 4A molecular sieve raw powder and kaolin.

2. The preparation method according to claim 1, characterized in that In step 1, the pretreatment method of industrial-grade nano-silicon carbide is specifically as follows: washing the industrial-grade nano-silicon carbide with water, alkali, and ethanol in sequence under ultrasound, centrifuging after each ultrasonic washing for 20 to 40 minutes, repeating 2 to 3 times with different solvents, the alkali used is a sodium hydroxide aqueous solution with a pH of 5; the hydrothermal temperature is 100°C, and the hydrothermal reaction time is 6 hours.

3. The preparation method according to claim 1, characterized in that: In step 1, the mass fraction of silicon carbide is 4~6%, and the mass ratio of Al(NO3)3, NaOH, H2O, TPAOH, TEOS and NaAlO2 is 1:0.6~3.3:52~60:4.9~7:2~4.3:0.04~0.

2.

4. The preparation method according to claim 1, characterized in that In step 2 (1), the concentration of the copolymer solution is 0.06-0.12 g L -1 The concentration of aluminum isopropoxide solution is 0.1~0.3 g L -1 ; The drying temperature is 60~80℃ and the drying time is 48~72h.

5. The preparation method according to claim 1, characterized in that In step 2 (2), in the ethanol solution of H2PtCl6, the mass concentration of H2PtCl6 is 0.1-10%; in the alumina powder loaded with single atomic platinum, the loading amount of Pt is 0.1-10%.

6. The preparation method according to claim 1, characterized in that In step 3, the concentration of the Co (NO3)2 solution is 0.02~0.1 mol L -1 The concentration of hexamethylenetetramine solution is 0.05~0.15 mol L -1 ; The vacuum drying temperature is 60℃ and the drying time is 10 h.

7. The preparation method according to claim 1, characterized in that In step 4, the washing method is to wash with deionized water and ethanol 2 to 3 times respectively, the drying temperature is 60°C, and the drying time is 10 hours.

8. The preparation method according to claim 1, characterized in that In step 5, the preparation method of ZIF-67 is as follows: according to the mass ratio of Co(NO3)2·6H2O and 2-methylimidazole of 1:1-5, a concentration of 0.05-0.15 mol L -1 The Co(NO3)2·6H2O methanol solution was injected into the -1 The mixture was added into a methanol solution of 2-methylimidazole and stirred at room temperature for 1.5-3.0 h. After the reaction, the precipitate was centrifuged, washed with ethanol, and vacuum dried at 60-80 °C overnight to obtain ZIF-67 powder.

9. The composite nanomaterial catalyst obtained according to the preparation method described in any one of claims 1 to 8.

10. The use of the composite nanomaterial catalyst according to claim 9 in microwave-assisted VOC catalytic oxidation, specifically comprising: introducing air and VOC tail gas, and heating the catalytic environment to an optimal catalytic reaction temperature of 250-320°C under microwave-assisted heating to carry out catalytic oxidation reaction.

Citation Information

Patent Citations

  • Silicon carbide modified catalyst used for microwave-heating catalytic oxidization of VOCs and preparation method thereof

    CN107961804A

  • Silicon carbide / ferroferric oxide synergetic molecular sieve loaded noble metal monatomic catalyst, preparation method and application of silicon carbide / ferroferric oxide synergetic molecular sieve loaded noble metal monatomic catalyst

    CN115090321A